Socio-demographic, economic and behavioral determinants of loss to follow-up status among human immunodeficiency virus-infected patients in southern Benin in 2020 - SALAMI, Lamidhi; ADJAFFON, Rebecca; Paraiso, Moussiliou; SOSSA, JÉRÔME CHARLES (My University, 2024)
Background: The recurrence of cases lost to follow-up constitutes a major concern for human immunodeficiency virus (HIV) care programs, particularly in Africa. The present study was carried out to determine the economic and sociobehavioral factors associated with the status of loss to follow-up among HIV-infected patients followed at the Suru Lere Zonal Teaching Hospital Center in Benin. Methods: This was a case-control study carried out with 41 cases selected for convenience and 82 controls retained according to a reasoned choice. Matching was done on the variables age (±5 years), sex and year of initiation of treatment. The data collected using questionnaires and counting sheets then entered using the Epi data 3.1 software were analyzed using the STATA 11 software. A multiple conditional logistic regression model at the 5% threshold was used to determine factors associated with “lost to follow-up” status. Results: In the sample, the average age of the people surveyed was 41±9 years for both cases and controls and women were predominantly represented (63.41%). The factors associated with the status of loss to follow-up were the nonexistence of a means of transport (p=0.008), the lack of nutritional support (p=0.01), incorrect knowledge about antiretroviral treatment such as “ARVs cure HIV/AIDS” (p=0.002) or “treatment can be stopped when you feel better” (p=0.014). Conclusions: This study revealed the significant association of “lost to follow-up” status with socio-demographic, economic and behavioral factors among people on ARV treatment. These results will lead to better guide the care of these patients and improve the performance of the AIDS control program.
Keywords: Loss to follow-up; A factors; HIV; Benin; ARV treatment; Determinants